2007
DOI: 10.1213/01.ane.0000261503.29619.9c
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Positive End-Expiratory Pressure on Functional Residual Capacity and Ventilation Homogeneity Impairment in Anesthetized Children Exposed to High Levels of Inspired Oxygen

Abstract: During the application of a very low PEEP of 3-cm H2O, FRC and ventilation distribution decreased significantly at an Fio2 of 1.0 compared with that at an Fio2 of 0.3. This decrease could be counterbalanced by the administration of PEEP of 6-cm H2O, indicating that a low level of PEEP is sufficient to maintain FRC and ventilation distribution regardless of the oxygen concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
70
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 28 publications
2
70
0
Order By: Relevance
“…9 By approximately two years of age, chest wall and lung compliance is similar to adults however, older infants and children continue to have a significantly smaller airway radius in proportion to their weight, less elastic retraction force, and a lower relaxation volume. [10][11][12] These factors all combine to predispose infants and children to atelectasis and hence an increased risk of VILI. Subsequently these populations show potential to benefit most from lung recruitment.…”
Section: Whose Lungs Do You Recruit?mentioning
confidence: 99%
See 3 more Smart Citations
“…9 By approximately two years of age, chest wall and lung compliance is similar to adults however, older infants and children continue to have a significantly smaller airway radius in proportion to their weight, less elastic retraction force, and a lower relaxation volume. [10][11][12] These factors all combine to predispose infants and children to atelectasis and hence an increased risk of VILI. Subsequently these populations show potential to benefit most from lung recruitment.…”
Section: Whose Lungs Do You Recruit?mentioning
confidence: 99%
“…[25][26][27] Increasing PEEP effectively allows the clinician to manipulate the functional residual capacity (FRC) and thereby minimise physiological deadspace, improving ventilation/perfusion mismatch and decreasing shunt fraction. 6,12,[28][29][30] Boriosi and colleagues chose this method of recruitment to assess the safety and efficacy of the open lung tool in paediatrics. Ultimately they used a modified version but found that oxygenation improved and peak inspiratory pressures were significantly reduced by 17% up to 12 hours post recruitment.…”
Section: Whose Lungs Do You Recruit?mentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, administering PEEP even in children with healthy lungs is mandatory in order to counterbalance the heterogeneity in ventilation-induced airway closure. Many studies have highlighted the beneficial effect of PEEP in restoring end-expiratory lung volume in children after general anesthesia [11], and to counteract the atelactasis induced by oxygen resorption [23]. In children with diseased lungs, PEEP improves lung function and oxygenation and potentially reduces the duration of mechanical ventilation [24].…”
Section: Lung Recruitmentmentioning
confidence: 99%